The Dividend Puzzle: A Corporate Action for Signal of High Prospect Companies In Indonesia - Suryawati, Baiq Nurul (LP3M Universitas Putra Bangsa, 2023)
This study was designed to examine the dividend policy variable as a moderating variable on stock prices. As a moderating variable, dividend policy will weaken or strengthen a series of other variables such as PBV, PER and EPS which are used to predict that there is a signal for a company's growth to increase stock prices as a signal that investors respond to. This research was conducted by running a simple regression to test the direct relationship of DPR with stock prices, multiple regression without DPR to examine the interaction of stock prices with market signal variables, and multiple regression to test the consistency of the significance of DPR's influence as a moderating variable with market signal variables and stock prices, then moderating regression or MRA to test the moderation between market signal variables and DPR as a moderating variable with stock prices. The results show that there is a direct significant effect between DPR and stock prices without involving other variables, but if you include market signal variables, PER becomes an insignificant variable. This means that PER does not affect stock prices. Furthermore, by placing DPR along with other variables, it appears that the positive relationship in the simple regression becomes insignificant. Therefore, a moderation regression was carried out where the results of the moderation regression showed that there was a pure moderating relationship between PBV and DPR, a moderating homologizer between PER and DPR, and quasi moderation between EPS and DPR. By looking at this relationship, it can be assumed that DPR, as a moderating variable, strengthens market signal variables in influencing stock prices. This also shows that the signal given by the company can be responded to by dividend policy.